2018
DOI: 10.2174/1381612824666180417122625
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic N-oxides - A Promising Class of Agents against Tuberculosis, Malaria and Neglected Tropical Diseases

Abstract: Heterocyclic N-oxides have emerged as promising agents against a number of diseases and disorders, especially infectious diseases. This review analyzes the emergence and development of this scaffold in the medicinal chemistry, focusing mainly on the discovery of new heterocyclic N-oxide compounds with potent activity against tuberculosis, malaria and neglected tropical diseases (i.e. leishmaniasis and Chagas disease). A number of heterocyclic N-oxides are described herein, nevertheless, the following chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Thus, the PCSK9-mediated degradation of LDLR increases LDL-C levels and promotes cardiovascular disease 42 . Interestingly, recent data have identified PCSK9 as a trigger for NAFLD 11 , 43 . Of note, the recent study shows that olanzapine treatment induces PCSK9-mediated dyslipidemia in patients with schizophrenia 44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the PCSK9-mediated degradation of LDLR increases LDL-C levels and promotes cardiovascular disease 42 . Interestingly, recent data have identified PCSK9 as a trigger for NAFLD 11 , 43 . Of note, the recent study shows that olanzapine treatment induces PCSK9-mediated dyslipidemia in patients with schizophrenia 44 .…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, PCSK9 is involved in the upregulation of triglyceride-rich lipoproteins and triglycerides through both LDLR-dependent and -independent pathways 13 . In addition, it has been demonstrated that high intrahepatic and circulating PCSK9 levels promote hepatic lipogenesis and lipid storage 11 , 43 , thus accelerating NAFLD pathogenesis. In this study, we demonstrated that metformin inhibits hepatic PCSK9 expression, in parallel to improving olanzapine-induced hepatic/hepatocyte steatosis in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A utilization of TEBAC as a phase transfer catalyst and Sc(OTf) 3 as a Lewis acid were crucial to increase the rate of the reduction and to avoid degradation of highly reactive diazonium salts 40 . A synthesized library of furoxan-based compounds represents an isosteric replacement of described drug candidates for the treatment of various neglected diseases including tuberculosis, leishmaniosis, schistosomiasis, and Chagas’ disease [ 83 , 84 , 85 , 86 ].…”
Section: Furoxansmentioning
confidence: 99%
“…The green chemistry methodologies available for their synthesis, which includes recyclable catalysts, microwave-assisted synthesis and water reactions, contribute to their attractiveness as drug development candidates [27]. Likewise, heterocyclic N -oxides have emerged as promising agents against several neglected and infectious diseases [28], and some quinoxaline derivatives have been reported as antihelminthic compounds against nematodes, cestodes, and trematodes [26,29].…”
Section: Introductionmentioning
confidence: 99%